Chronic osteomyelitis of maxilla in an immunocompetent patient: A rare case report (Indian Journal of Case Reports, 2018)
Osteomyelitis is an acute and chronic inflammation of a medullary portion of bone along with cortex and periosteum. Osteomyelitis is more common in developing countries. Among the other bacterial infectious diseases, osteomyelitis is the most difficult to treat. We hereby report a rare case of osteomyelitis of maxilla in a middle-aged immunocompetent male patient who was treated with subtotal maxillectomy, and later, the defect was closed with split-thickness skin graft.